Expect the unexpected: a case report of bacterial meningitis causing Guillain-Barré syndrome in an immunocompetent person - Chua, Joycel Angelique F. (International Journal of Research in Medical Sciences, 2023)
This is the case report of a 36-year-old male presenting as acute onset of progressive bilateral lower extremity weakness, initially managed as a case of Guillain-Barré Syndrome (GBS). However, his cerebrospinal fluid tested positive for Neisseria meningitidis Y, Neisseria meningitidis W135, Streptococcus group B antigen, and Streptococcus pneumoniae. The patient was later treated for bacterial meningitis. Most cases of GBS are preceded by an upper respiratory infection or gastroenteritis. There are only a few reported cases of bacterial meningitis occurring coincidentally with GBS, much more in an immunocompetent individual. This is a rare case of such with good patient recovery and outcome.